Studi Pengaruh Jenis Katalis, Waktu Reaksi dan Penurunan Bilangan IODINE pada Pembuatan Cocoa Butter Substitute dengan Proses Hidrogenasi Minyak Kelapa - Hernowo Widodo; Lisa Adhani; Elvi Kustiyah; Ilham Santoso (Jurnal Jaring SainTek, 2019)
Vegetable fat can be used as a base for making chocolate butter substitutes in making chocolate coatings. The product is also called hard butter can be obtained using coconut oil. The fats used as a substitute for cocoa butter are coconut oil, palm oil and palm kernel oil that have been obtained by hydrogenation, the hydrogenation process is used to reduce iodine numbers to obtain oil in the form of plastic solids and to increase the consistency of oils and fats to reduce color and smell and to improve stability. In this study the hydrogenation reaction of coconut oil experienced an increase in speed when the commercial catalyst composition of Pricat 9910 was added with a 0.75 gram nickel catalyst and 0.75 grams of silica which was characterized by a drastic decrease in iodine number from 12.12 to 1.94 gr I2 / 100 gr example in the reaction time of 8 hours, It contained in hydrogenated coconut oil did not change or damage when the catalyst composition used in the hydrogenation process is increased.